Mucocutaneous manifestations of HIV/AIDS infection: literature review - Mutia Devi; Muhammad Izazi Hari Purwoko; Suroso Adi Nugroho; Yulia Farida Yahya; Indah Astri Aryani; Kiki Septiafni (Explorer Front, 2022)
Mucocutaneous manifestations are the first recognized human immunodeficiency virus (HIV) infections. More than 90% of HIV-infected patients develop at least one or more types of typical or atypical skin lesions during the disease. Mucocutaneous manifestation can also indicate the progression of HIV infection and cluster of differentiation 4 (CD4) cell count as an indicator of the development of acquired immunodeficiency syndrome (AIDS). It is important to know mucocutaneous manifestations and their correlation with the patient’s immune status to provide appropriate treatment to improve the patient’s quality of life.